(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the analysis of the draft Law «On forensic activities» in terms of secure social status of the assessor and the consolidation of authority for various kinds of expertise within the Ministry of Justice. The authors studied the bill are compared with other legal acts and policy documents are discrepancies in them. The conclusions of the authors formulate concrete proposals to improve the legislation of forensic activity, in terms of reducing the reference rules. Key words: forensic activities, management of state assets, the Chamber of private enforcement experts, discretionary powers, corruption potential.